The Distribution of Advanced Practice Nurses Within the Psychiatric Workforce. (January 2020) - Beck, Angela J.; Page, Cory; Buche, Jessica; Gaiser, Maria
OBJECTIVE: To examine the size and distribution of the advanced practice psychiatric nurse workforce relative to the total psychiatry workforce to determine whether nurses are predominantly working in areas with higher or lower levels of behavioral health specialists.METHODS: State-level data for psychiatric nurses were obtained from the American Nurses Credentialing Center, and included mental health psychiatric nurse practitioners, adult psychiatric nurse practitioners, child psychiatric clinical nurse specialists, and adult psychiatric clinical nurse specialists. Supply estimates of the full psychiatry workforce were calculated for comparison purposes. State population estimates were obtained from U.S. Census Bureau data. State workforce estimates were converted to a 1:100, 000 provider-to-population ratio to analyze the density of providers across states.RESULTS: In 2018, the psychiatric workforce supply was estimated to be composed of 66, 740 providers, including psychiatrists ( n = 47, 046; 71%), psychiatric nurses ( n = 17, 534; 26%), physician assistants ( n = 1, 164; 2%), and psychiatric pharmacists ( n = 966; 1%). Overall, psychiatric providers appeared to be most densely concentrated in the northeast region of the United States. A dearth of providers was most pronounced within areas in the 12-state Midwest region, southern states, California, and Nevada. The average concentration of psychiatric workers was 22.61 per 100, 000 population.CONCLUSIONS: The findings of this study find inconsistent pattern of how psychiatric nurses are distributed relative to the rest of the workforce, but reinforce the idea that they are essential in addressing care needs in areas with low concentrations of psychiatry specialists—especially if they are authorized to work to the full extent of their training/education.